2013
DOI: 10.1108/jocm-04-2012-0047
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming organizational inertia to strengthen business model innovation

Abstract: Purpose – This study aims to examine how open innovation can be effective in changing organizational inertia to create business model innovation and improve firm performance. It also seeks to explore whether the existence of open innovation has a mediating effect and influence. Design/methodology/approach – This study constructs a theoretical model to explore the relationship between latent variables and uses a questionnaire to collect research data. In the conceptual framework, organizational inertia is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
165
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(186 citation statements)
references
References 67 publications
5
165
2
4
Order By: Relevance
“…However, inter-firm organization has most significant positive impact on innovation performance of SMEs. Huang et al (2013) showed that open innovation has a significant mediating effect on the relationship between organizational inertia and business model innovation, and the relationship between organizational inertia and firm performance. Kim and Park (2010) found that, among Korean SMEs, external R&D has a positive and significant effect on innovation output, but external ideas have a negative effect and external knowledge has no impact.…”
Section: Open Innovation Performancementioning
confidence: 99%
“…However, inter-firm organization has most significant positive impact on innovation performance of SMEs. Huang et al (2013) showed that open innovation has a significant mediating effect on the relationship between organizational inertia and business model innovation, and the relationship between organizational inertia and firm performance. Kim and Park (2010) found that, among Korean SMEs, external R&D has a positive and significant effect on innovation output, but external ideas have a negative effect and external knowledge has no impact.…”
Section: Open Innovation Performancementioning
confidence: 99%
“…Although Domingo (2008) argues that newsrooms are prevented from innovation through inertia, this study comes to the conclusion that a multi-platform strategy leading to the implementation of a central news desk is connected to innovative values of journalists, which in turn changes working procedures. A multi-platform strategy, as well as other structural newsroom features, is effective in overcoming procedural inertia, which is essential for the news organization and its innovative capacities (Corstjens et al, 2011;Huang, Lai, Lin, & Chen, 2013). However, overcoming routine rigidity may not be sufficient for "real" innovation reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Two publications in available literature on OBMI discussed how OI can be effective in creating BMI [13,33]. Both studies used a quantitative approach to explore the implications of external knowledge sourcing for BMI and firm performance [13] or firm growth "as a proxy for BMI success" [33], respectively.…”
Section: Obmi Effectsmentioning
confidence: 99%
“…and to reduce the time-to-market for new products [12][13][14]. By combining internal and external sources of innovation, firms gain access to new innovations, new customers, new ways of commercialization and additional markets [12,13].…”
mentioning
confidence: 99%